2012
DOI: 10.1007/s00345-012-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of C-TRUS with multiparametric MRI: potential for improving detection of prostate cancer

Abstract: Combination of multiparametric MRI and C-TRUS seems to improve detection of prostate cancer, especially in high-risk patients. Detection rates of C-TRUS in this study could confirm those of the primary C-TRUS studies. The benefit of MRI is the additional visualization of the tumor extension. The technique is an option for pre-biopsied patients. Both imaging methods often fail to predict correct tumor stage, but further studies are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
2
9
0
1
Order By: Relevance
“…These results were able to be confirmed in another study with 20 patients. Prostate cancer was able to be detected via biopsy of suspicious areas in 11 of 20 patients (58 %) [20]. A comparison of the results of targeted biopsy of suspicious areas and systematic biopsy has not yet been published.…”
Section: Computer-assisted Ultrasoundmentioning
confidence: 97%
“…These results were able to be confirmed in another study with 20 patients. Prostate cancer was able to be detected via biopsy of suspicious areas in 11 of 20 patients (58 %) [20]. A comparison of the results of targeted biopsy of suspicious areas and systematic biopsy has not yet been published.…”
Section: Computer-assisted Ultrasoundmentioning
confidence: 97%
“…In the remaining 500 samples, C-TRUS showed a sensitivity and specificity of 79 and 99%, respectively. In the latest study, Strunk et al [17] combined C-TRUS with mpMRI in a population of 20 patients with elevated prostatespecific antigen (PSA). C-TRUS detected suspicious lesions in 20/20 patients whereas mpMRI detected suspicious lesions in 17/20 patients.…”
Section: Computerized-transrectal Ultrasoundmentioning
confidence: 98%
“…Novel ultrasound-based modalities (e.g., elastography, contrast-enhanced ultrasound, and computer-assisted ultrasound) are now available to urologists at a lower cost than cross-sectional imaging [8,9,11]. Some of these, notably computer-assisted analysis, sonoelastography and contrastenhanced ultrasound, have been investigated and the promising results published [8][9][10].…”
mentioning
confidence: 99%
“…Some of these, notably computer-assisted analysis, sonoelastography and contrastenhanced ultrasound, have been investigated and the promising results published [8][9][10]. It has been shown that targeted mpUS can achieve positive biopsy rates and significant cancer diagnosis rates equivalent to that seen using mpMRI targeted techniques in biopsy naive patients [10][11][12][13]. Data from a 12-year follow-up of the artificial intelligence protocol provides evidence of the possibility of monitoring patients by a big-data, artificial intelligence approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation